(untitled) (TERRA LATINOAMERICANA, 2023)
The Mixteco River basin is located in the state of Oaxaca, Mexico and comprises a total area of 6 559.20 km2, which shows a strong degradation of its natural resources, derived mainly from anthropic actions associated with poor management of its natural resources. Thus, the goal of this research is to evaluate the runof f behavior with the SWAT (Soil and Water Assessment Tool) model in the Mixteco River basin using the soil spatial distribution from INEGI (Instituto Nacional de Estadística y Geografía) and that obtained through technique of DSM (Digital Soil Mapping) technique. The modeling with INEGI (ModINEGI) corresponds to the soil map of the series II scale 1:250 000, and the modeling with DSM (ModDSM) was obtained from the environmental covariates. The SWAT model performance evaluation indicators during the calibration phase were R2 = 0.88 and NSE = 0.87 for ModDSM and R2 = 0.85 and NSE = 0.85 for ModINEGI. However, during the validation period, the ModDSM results (R2 = 0.83 and NSE = 0.81) were better than those of ModINEGI (R2 = 0.83 and NSE = 0.61). Therefore, the results indicate that the spatial variation of the soil types obtained through the DSM technique in combination with the vegetation cover and the distribution of slopes at the basin level, allow the SWAT model to simulate the adequate surface runof f behavior.